Connexin26 Modulates the Radiosensitivity of Cutaneous Squamous Cell Carcinoma by Regulating the Activation of the MAPK/NF-κB Signaling Pathway - Sun, Minqiong; Li, Yuan; Qian, Jing; Ding, Siwei; Sun, Mingyu; Tan, Bowen; Zhao, Ye (Frontiers in Cell and Developmental Biology, 2021)
Previous studies have confirmed that the gap junction protein Connexin26 (Cx26) is specifically expressed in human skin tissue. Cx26 can transmit radiation-induced damage signals. However, no study has yet reported whether Cx26 expression affects the radiosensitivity of human skin squamous cancer cells or the mechanism by which this occurs. In this study, we found that human skin squamous cell carcinoma cells (A431 cells) expressed significantly more Cx26 and were more sensitive to radiation compared to normal human keratinocytes (HaCaT cells). Knockdown of Cx26 in A431 cells (A431Cx26-/-) decreased radiosensitivity relative to control cells and altered the expression of key proteins in the MAPK and NF-κB signaling pathways. These results demonstrate that Cx26 expression might play an important role in mediating radiation damage in A431 cells and could serve as a potential target for clinical radiotherapy for cutaneous squamous cell carcinoma.